Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages (5) Home Helps. Only six counties appear to make use of this provision. (6) Provision of milk or food during the last three months of pregnancy and during lactation. This is stated to be provided in thirty-two counties. (7) Complicated Midwifery. (a) The fees of doctors called in by midwives for an "emergency" in connection with a confinement must be paid, if necessary, in whole or in part. This being a statutory obligation, is in force in all counties. (b) The fee of a consultant called in by a doctor for a complicated midwifery case or for puerperal infection. Twenty-seven counties note that they use this power. (c) Skilled nursing for patients confined at home. We can only find that six provide this. This figure includes only one or two places who employ special nurses. All the rest are grants to local nursing associations for more than simply puerperal sepsis cases. (d) Bacteriological examination in cases of puerperal infection. This is arranged for in eleven counties. We consider this may be an under-statement and that most counties now have these facilities when occasion arises though they appear not to be used to the full. (8) Convalescent Home Treatment for mothers after confinement. This is only stated to be used in two counties. (9) District Nursing Associations. Payments can be made for midwifery and maternity nursing, or for the nursing of puerperal fever. Assistance can be given towards the establishment of new Nursing Associations in areas where a midwife is required. It is stated that this is made use of in thirty-six counties. (10) Provision can also be made for assisting unmarried mothers and their children. This provision appears to be used by thirteen Councils. We have not included Public Assistance accommodation except when special facilities are attached, nor diocesan and voluntary homes unless a grant is made by the Local Authorities. Roughly speaking, it appears that about twenty-three County Councils are aiding the Maternity Service of the district by putting into force half or more of the services they have power to provide. (7) 292/824/1/58